Why Low Inequality Spurs Growth: Savings and Investment by the Poor - Nancy Birdsall; Thomas C. Pinckney; Richard H. Sabot (Inter-American Development Bank, Office of the Chief Economist, 1996)
This paper discusses the ways in which macroeconomic developments can put stress on banks, and in extreme cases lead to banking crises. There are many ways in which this can occur, and no specific mechanism is endorsed. These macroeconomic causes of bank vulnerability and crisis have important implications for regulatory regimes, and for macroeconomic policy itself. Much of the discussion emphasizes the need to set monetary policy with an eye on the state of the domestic banking system.
Keywords: 330